If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(3x + -4) = 2x(3x + 8) Reorder the terms: 2x(-4 + 3x) = 2x(3x + 8) (-4 * 2x + 3x * 2x) = 2x(3x + 8) (-8x + 6x2) = 2x(3x + 8) Reorder the terms: -8x + 6x2 = 2x(8 + 3x) -8x + 6x2 = (8 * 2x + 3x * 2x) -8x + 6x2 = (16x + 6x2) Add '-6x2' to each side of the equation. -8x + 6x2 + -6x2 = 16x + 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -8x + 0 = 16x + 6x2 + -6x2 -8x = 16x + 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -8x = 16x + 0 -8x = 16x Solving -8x = 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -8x + -16x = 16x + -16x Combine like terms: -8x + -16x = -24x -24x = 16x + -16x Combine like terms: 16x + -16x = 0 -24x = 0 Divide each side by '-24'. x = 0 Simplifying x = 0
| 21-y=26 | | 14+0.3333x=40 | | 3x/7=2/7=2 | | 0.1=cos(x) | | 7/4-7/3 | | 8n^2-10n-3=0 | | 5/3-4 | | 3(x+10)=2x+30 | | -3x^3-9x^2-6x=0 | | 2(4x-9)=7(x-2) | | (1/3)(2/5)-45 | | 42-3x=12-9 | | 4=3w-5 | | x+50+2x-8=87 | | -10=2+2u | | -4+6x+2x=14+6 | | -1/2=1/5v-4/3 | | 325+5x=9480 | | 3v-7=8 | | 5m^2-7m+6=0 | | -26=5x+4 | | 7h-23=40 | | 45-1/3-5/5 | | 2(2x+4)+6=3+3(x-7) | | -3/4u-2/3=-3/4 | | 18n^2-48n-96=0 | | 1/2x-16=32 | | 56v^2+464v+128=0 | | 3(w+4)=-9w-24 | | 3x-4x+3x-6= | | 4x+3=-5x+3 | | x/5-6=10 |